Synthesis and Characterization of some new copolymers as drag reduction agent for study rheology light Basra crude oil (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
A series methods used to increase the flow of crude oil through the pipes to reduce the economic cost and increase the flow rat of crude oil, the most important of these methods is the addition of small amounts of polymers to reduce the drag reduction flow crude oil, In this study, three polymers of different structures were prepared , P1 linear condensation polyester and different branching functional group by free radical polymerization P2 and P3, This polymers were characterization by using different techniques such as FTIR, 1H-NMR and 13C-NMR, The polymers were added as drag reducing agent for crude oil in different concentrations (100-600 ppm) at 35oC , The percentage drag reduction was calculated by using circulation flow system device with different temperatures(35,45 and 55oC).